STRUCTURAL RELIABILITY ANALYSIS USING DETERMINISTIC FINITE ELEMENT PROGRAMS - BECK, ANDRÉ T. (2006)
THE PAPER SHOWS HOW STRUCTURAL RELIABILITY ALGORITHMS CAN BE INCORPORATED INTO DETERMINISTIC (COMMERCIAL) FINITE ELEMENT CODES AND USED TO PERFORM NUMERICAL STRUCTURAL RELIABILITY ANALYSIS BASED ON FINITE ELEMENT MODELS OF A STRUCTURE. A STRUCTURAL RELIABILITY MODULE IS DEVELOPED AND LINKED TO THE ANSYS FINITE ELEMENT PROGRAM, CREATING A CUSTOMIZED VERSION OF THE PROGRAM. STRUCTURAL RELIABILITY ANALYSIS CAN BE PERFORMED IN THE ANSYS ENVIRONMENT, AND INVOLVES CONSTRUCTION OF A PARAMETRIC Â¯NITE ELEMENT MODEL, DEFINITION OF RANDOM PARAMETER DISTRIBUTIONS, DEÂ¯NITION OF A LIMIT STATE FUNCTION BASED ON FINITE ELEMENT RESULTS, AND SOLUTION FOR THE FAILURE PROBABILITY. NUMERICAL EXAMPLES INVOLVING TRUSS AND FRAME STRUCTURES ARE STUDIED. AN APPLICATION EXAMPLE - STRUCTURAL RELIABILITY ANALYSIS OF AN EYE-BAR USPENSION BRIDGE - IS ALSO PRESENTED.